A General Assessment Upon Postgraduate and Phd Theses Prepared Related to Digital Transformation in Turkey - Altay, Ahmet; Zan, Burcu Umut (Bobcatsss, 2023)
In recent years, mainly in information and communication technologies, cloud computing, artificial intelligence, internet of things, big data, advanced robotics, etc. developments in technologies have revealed the concept of digital transformation. In other words, digital transformation is a transformation process that occurs when the internet, communication, informatics, sensor, automation, artificial intelligence - machine learning and robotic technologies significantly affect and change all social structures and systems. It is observed that this process deeply affects all social, cultural and economic institutions and structures in the world. In short, an intense digital transformation is taking place in every field where people and society take part. It is not possible for the scientific world to remain irrelevant to the issue of digital transformation, which has such a great impact. Indeed, when the literature related to digital conversion is assessed, it is seen that there were many academic works published in as papers, articles, books, projects, thesis and etc. in different branches of science both in the World and in Turkey. In these studies, it is seen that each discipline examines "digital transformation" from its own perspective. In this research graduate theses, which were prepared between the years 2013-2020, digital transformation was examined. Purposeful sampling method was used in this study, which was conducted in the documentary scanning model. The sample of the study consists of 43 theses archived by the Higher Education Council's Publication Documentation Department. "Thesis Evaluation Form" was prepared by the researchers to analyse thesis. 43 theses within the scope of the research are classified according to their types, subjects; distribution according to publishing years; distribution according to affiliated institutes and branches of science; distribution according to research methods used; distribution according to measurement tools and distribution according to sample groups were collected with using evaluation form. The findings obtained in the research were interpreted based on percentage and frequency values which were shown on tables and graphs. According to the results of the research, it has been determined that there has been a huge increase in the number of theses prepared on digital transformation since 2018, that there are more master’s degree theses than doctoral theses on this subject, and that quantitative research methods are used the most in theses and scales are used as measurement tools. In addition, it has been determined that the areas that mainly focus on public institutions, businesses and universities are discussed in the theses.